ChemInform Abstract: Pd‐Catalyzed Aerobic Direct Olefination of Polyfluoroarenes. Issue 43 (21st October 2014) - He, Chun‐Yang; Qing, Feng‐Ling; Zhan, Xingang
Abstract Optimal conditions are elaborated for the synthesis of polyfluoroarene‐alkene structures via direct olefination of fluoroarenes.